Mental Disorders in Individuals With Exercise Addiction—A Cross-Sectional Study - Meyer, Maximilian; Sattler, Isabel; Schilling, Hanna; Lang, Undine E.; Schmidt, André; Colledge, Flora; Walter, Marc (Frontiers in Psychiatry, 2021)
Background and Aims: Exercise addiction has not yet been designated as an addictive disorder in the DSM-5 due to a lack of detailed research. In particular, associations with other psychiatric diagnoses have received little attention. In this study, individuals with a possible exercise addiction are clinically assessed, in order to establish a profile of co-occurring psychiatric disorders in exercise addicts. Methods: One hundred and fifty-six individuals who reported exercising more than 10 hours a week, and continued to do so despite illness or injury, were recruited for the study. Those who met the cut-off of the Exercise Dependence Scale (n=32) were invited to participate in a screening with the Structured Clinical Interview for DSM-5 (SCID-5-CV) and personality disorders (SCID-5-PD). Additionally, an interview based on the DSM-5 criteria of non-substance-related addictive disorders was conducted to explore the severity of exercise addiction symptoms. Results: 75% of participants fulfilled the criteria for at least one psychiatric disorder. Depressive disorders (56.3%), personality disorders (46.9%) and obsessive-compulsive disorders (31.3%) were the most common disorders. Moreover, there was a significant positive correlation between the number of psychiatric disorders and the severity of exercise addiction (r = .549, p = .002). Discussion: The results showed a variety of mental disorders in individuals with exercise addiction and a correlation between the co-occurrence of mental disorders and the severity of exercise addiction. Exercise addiction differs from other addictive und substance use disorders, as obsessive-compulsive (Cluster C), rather than impulsive (Cluster B) personality traits were most commonly identified. Conclusions: Our results underscore the importance of clinical diagnostics, and indicate that treatment options for individuals with exercise addiction are required. However, the natural history and specific challenges of exercise addiction must be studied in more detail.